Interpretation of gender relations in modern Islamic countries (Journal of Philosophy Culture and Political Science, 2019)
The article discusses gender relations in Muslim society. Was given comparative analysis of feminist movements in Muslim society and the levels of gender relations in these countries. The dynamics of gender stereotypes in socio-cultural and religious contexts and their influence on feminist movements in Muslim society are determined. The social role and marital status of women, education, participation in social structures and movements and observance of gender inequality in various spheres of life in Muslim countries are considered. The article analyzes gender relations of Muslim states in particular in Turkey and Egypt. Was carried out comparative analysis of the situation of women in the pre-Islamic Turkish society, during the Ottoman Empire and in the modern Turkish Republic. Has also been made a brief analysis of gender issues in the Arab Republic of Egypt from the end of the twentieth century to the present.Key words: Gender, feminism, Islam, women, religion, culture, state, Muslim. society.